Electrodynamic theory of superconductors - Zhou, Shu-Ang (London P. Peregrinus on behalf of the Institution of Electrical Engineers, 1991)
This book presents a unified and comprehensive theoretical treatment of electromagnetic, thermal and mechanical phenomena in superconductors. Introduces basic concepts and principles with particular emphasis on general methodology.
Electronic reproduction.
Keywords: Superconductors; Electrodynamics; Electronic books